-3(2x+1)+x=2-(4x-2)

Simple and best practice solution for -3(2x+1)+x=2-(4x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2x+1)+x=2-(4x-2) equation:


Simplifying
-3(2x + 1) + x = 2 + -1(4x + -2)

Reorder the terms:
-3(1 + 2x) + x = 2 + -1(4x + -2)
(1 * -3 + 2x * -3) + x = 2 + -1(4x + -2)
(-3 + -6x) + x = 2 + -1(4x + -2)

Combine like terms: -6x + x = -5x
-3 + -5x = 2 + -1(4x + -2)

Reorder the terms:
-3 + -5x = 2 + -1(-2 + 4x)
-3 + -5x = 2 + (-2 * -1 + 4x * -1)
-3 + -5x = 2 + (2 + -4x)

Combine like terms: 2 + 2 = 4
-3 + -5x = 4 + -4x

Solving
-3 + -5x = 4 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-3 + -5x + 4x = 4 + -4x + 4x

Combine like terms: -5x + 4x = -1x
-3 + -1x = 4 + -4x + 4x

Combine like terms: -4x + 4x = 0
-3 + -1x = 4 + 0
-3 + -1x = 4

Add '3' to each side of the equation.
-3 + 3 + -1x = 4 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = 4 + 3
-1x = 4 + 3

Combine like terms: 4 + 3 = 7
-1x = 7

Divide each side by '-1'.
x = -7

Simplifying
x = -7

See similar equations:

| 9x-10y=-13 | | 1/4(-8g+24)=g | | 5v-4-6=15+4v | | 4x+14=11x-2 | | 2x+63=9 | | ((1/t)-1)/(t-1) | | 7(4n+4)-10= | | -40n-43=3n | | 8n+8(n+7)=-35+3n | | ((x^8y^-4)/(16^(4/3)))^(-1/4) | | Y=-8x^2-10x+3 | | 6X+16=2x-12 | | 142.09=6s+17.47 | | -5x+9=-4x+8-x-3 | | 14/15x=12 | | -14-v=1+2v | | 5v^2-9=81 | | 3(w-7)-3=-5(-4w+6)-5w | | 2-2y=14+4y | | 2m/7=6/21 | | -25+6x=-3(7-2x) | | 4y+9-6y=15-8y | | 5n-7=7(n-1)-2n | | 1790/0.08 | | -16t^2+124t-84=0 | | 10/13x=4 | | 1+6b+4b-4=4b+7b | | 4x^2(x^2+6xy-7y^2)= | | 5(x+2)+x=6(x+3)-4 | | -7+9x=20 | | -17=13+-10n | | X^2-8x-16=81 |

Equations solver categories